Ketidakadilan Hukum di Indonesia Dalam Penanganan Kasus Nenek Asyani - Sarwandari, Aninda Putri; Fauzi, Agus Machfud (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes legal injustice in Indonesia with a case study of Nenek Asyani, a poor woman who was accused of stealing seven teak logs belonging to Perhutani in Situbondo, East Java. Through a qualitative descriptive approach, this study explores the inequality in the application of the law between the poor and the elite, who often receive lighter legal treatment even though they are involved in major crimes such as corruption. Based on Aristotle's theory of justice and the perspective of the sociology of law, it is found that the legal system in Indonesia tends to be blunt at the top and sharp at the bottom, reinforcing structural injustice. This analysis highlights the importance of distributive and corrective justice in the context of fairer legal application. The results of this study provide recommendations for improving the legal system in Indonesia through a humanist and progressive approach, in order to create substantive justice for all levels of society.